Introduction - The quest for a good life: Contributions from the Arctic towards a theory of wellbeing - Toivanen, Reetta; Stammler, Florian (2021)
Desire for what is good—and for a good life—is one of the human universals spanning across all societies and cultures. Yet, how people imagine a good life differs significantly according to the individual, and it also depends on numerous social, political, cultural, economic and geographical variables. In this book we explore what a good life looks like for young people in a place that, at first glance, may appear difficult or hostile for human inhabitation: the Arctic region. The Arctic is often portrayed in popular and scientific literature as a frontier characterized by the catastrophic impacts of a changing climate and resource extraction. This adds to the image of the Arctic as a region that is ill-fit for human wellbeing and emplacement, where outmigration should be the default goal of the young generation. In a globalized world, however, youth have more choices than ever where to emplace themselves and how to realize their dreams. This introduction focuses on three principal questions from a theoretical vantage point rooted in the anthropology of wellbeing. What affordances does the Arctic offer for a good life as young people make their choices? What can empirical evidence from working with young people in the Arctic contribute to our general understanding of wellbeing as a concept in the social sciences? Which factors make Arctic towns attractive as places for youth to realize their dreams in life? The chapters in this volume all approach these questions in their own way with empirical evidence from various places in the Arctic. Peer reviewed